ON RECOVERY OF A FRANKLIN SERIES FROM ITS SUM - Keryan, K.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In an earlier work of author a theorem on recovery of Franklin series from its sum under some conditions was obtained. In present article it is shown that to some extent these conditions are necessary.